Out of the shadows: Chronic pain in Canadian Armed Forces veterans — Proceedings of a workshop at the 2019 Forum of the Canadian Institute for Military and Veteran Health Research. Issue 1 (1st January 2020) - Thompson, James M.; Heber, Alexandra; Zacharias, Ramesh; Besemann, Markus; Gupta, Gaurav; Hapidou, Eleni; Buckley, Norm; Lamoureux, Daniel; Begley, Kimberly
ABSTRACT: This commentary summarizes proceedings of a workshop on chronic pain in military personnel and veterans (released personnel) at the Annual Forum of the Canadian Institute for Military and Veteran Health Research in Gatineau and Ottawa on October 22, 2019. The extent and impact of chronic pain among Canadian Armed Forces (CAF) veterans and their families is significant and has been underappreciated, largely due to limited disclosure by serving and veteran military personnel, stemming from a fear of stigmatization. Living with pain is seen as a fact of life in military cultures, something to be endured and not discussed. Though progress is being made in reducing the stigma of mental illness, the discourse on chronic pain remains censored. This workshop's goal was to bring the discussion of chronic pain out of the shadows in the search for ways to help veterans and active service personnel living with chronic pain. Many points of view were brought forward at this first national Canadian multidisciplinary gathering of researchers, veterans with lived experience, clinicians, and policymakers. A CAF member described his lived experience with constant chronic pain. Clinicians described aspects of chronic pain in military personnel and veterans whom they treat in their clinics. Dr. Ramesh Zacharias described the new Chronic Pain Center of Excellence for Canadian Veterans that will be established with funding from Veterans Affairs Canada. Dr. Norman Buckley highlighted collaboration with the existing Chronic Pain Network funded by the Canadian Institute for Health Research. Audience members identified a diverse variety of issues.